Effects of Benthic Burrows on Hyporheic Exchange - Kaiwen Zhang; Guangqiu Jin; Guangming Zhang; Hongwu Tang; Siyi Zhang; Hexiang Chen; D. A. Barry; Zhongtian Zhang (Water Resources Research)
Abstract Macrobenthic invertebrates are widely distributed on sediments, and the micro‐morphology such as burrows and sand mounds due to their bioturbation activities can cause substantial changes in hyporheic exchange (HE). This study explores the characteristics of HE induced by benthic burrows through flume experiments and numerical simulations, focusing on the influence of burrow depth, mound height, and inter‐burrow distance. Our findings reveal that burrows enhance HE by forming preferential flow conduits. With the increased interfacial pressure drop and the newly formed circulations, the pore water tends to outflow through burrow sidewalls along the preferential paths in greater velocity under the enhanced advection, and the “pumping” effects persist even below the burrow depth. The pore water flux increased by 10.76 times on the burrow sidewall at most. Eddies are induced by mounds above the streambed, changing the inflow/outflow patterns on the interface. The interfacial exchange rate below eddies is decreased while the solute can inflow within more distant ranges away from burrows. The effects of mound height carry out in the shallow streambed, and quickly decrease as penetration depth increases. Variations in inter‐burrow distance affect the transition process of HE from advection‐ to dispersion‐dominated. As the distance increases, the solute transport is promoted first due to the enhanced advection, and then decreased with the weakened advection and the larger proportion of the dispersion. This study provides important insights into the key mechanism of HE, highlighting the critical role of benthic burrows in aquatic ecosystems.